Investigation Purchase Decision Through Brand Trust, Brand Image. Price. Quality of Product: A perspective Service Dominant Logic Theory - Juliana Juliana; Rudy Pramono; Sandra Maleachi; Innocentius Bernarto; Arifin Djakasaputra (Kontigensi : Jurnal Ilmiah Manajemen, 2021)
Logically, service dominant logic tends to be more integrative than goods dominant logic. This is related to the basic proposition related to co-creation which involves active customer involvement and interaction with suppliers in every aspect of product consumption and product design. This study aimed to analyze the factors that might affect the purchasing decision of Hotpot Haidilao restaurant. This study used five variables which are brand trust, brand image, price, quality og product, purchase decision.The phenomenon of the growing food service business in the city Jakarta, which also influences consumer purchasing decisions, especially on the selection of a place to eat is the background of this study. In specifically, this research was conducted by developing a model foranalyze consumer purchasing decisions for food products and drinks at the restaurant. The sampling technique used convenience sampling with 300 respondents. Data collection techniques using googleform. The data analysis technique used is PLS-SEM. The results of the analysis conclude the purchase decision of Hotpot Haidilao restaurant was affected by brand image, brand trust, quality of product and price.